Between Text and Context: The Philosophical and Sociological Basis of Girls' Hijab Rights in Indonesian and Malaysian Islamic Inheritance Law - Atika Sandra Dewi; Mhd Nurhusein Daulay (JURNAL AKTA, 2026)
This study aims to comparatively analyze the application of a daughter's hijab rights to her father's brother in the Islamic inheritance law systems of Indonesia and Malaysia. Although both countries base their family law on the Shafi'i school of thought, the practice and interpretation of daughters' inheritance rights show significant differences, particularly in determining the position of daughters as obstacles (ḥājib) for lateral heirs. This study uses a qualitative approach with a normative-comparative legal research type. The results show that the Islamic inheritance law system in Indonesia tends to use a contextual and progressive approach, which allows for the strengthening of daughters' rights through a more responsive interpretation of the values of substantive justice and gender equality. In contrast, the legal system in Malaysia shows a more rigid and textual normative tendency, thus limiting the scope for inheritance law reform despite changes in the social structure of society. The novelty of this study lies in the cross-national comparative analysis that places the concept of hijab within the perspective of maqāṣid al-sharī'ah and modern social dynamics, which have rarely been discussed in depth. This study concludes that a re-reading of Islamic inheritance law by emphasizing the objectives of sharia and the principles of substantive justice is an urgent need to ensure the relevance and justice of inheritance law in the context of contemporary Muslim society.